Optical fiber sensors integrated in polymeric foils - Silva, A. F. (2009)
Optical sensors have hit their maturity and a new kind of systems is being developed. This paper deals with the development of a new sensing structure based on polymeric foils and optic fiber sensors, namely the Fiber Bragg Grating sensors. Sensor integration in polymeric foils, using industrial process is the proposed goal. To achieve this goal, Finite Element Analysis was used for prototype modeling and simulation. The model was subjected to loads and restraints in order to retrieve information about stress distribution and displacement of specific points. From the simulation was possible to predict the sections where the sensor should be positioned. A prototype was then fabricated using industrial processes. Tests indicate that the polymeric foil influence on the sensor performance may exist. However, the prototype was able of transferring the full deformation to the optical sensor. Moreover, the optical sensor, which is incorporated in the polymeric foil, is fully functional with high sensitivity, 0,6 picometer by microstrain, allowing deformation measurements, up to 1,2 millimeter.